Penyuluhan Kalkulasi Harga Pokok Produksi Biaya Penuh Untuk Penentuan Harga Jual UMKM di Desa Majau - Mia Laksmiwati; Dicky Arisudhana; Sugeng Priyanto; Indah Rahayu; Qodariah (Universitas Lancang Kuning, 2023)
Abstract This community service activity was carried out in Majau Village, Pandeglang Regency, Banten Province. The participants in this activity are Micro, Small and Medium Enterprises (MSMEs) who are domiciled in Majau Village, Pandeglang Regency. Majau Village, Pandeglang Regency has community potential and resources that support entrepreneurship. This condition is evidenced by the increasing number of business actors in the village. In line with the increase in the number of business actors, they faced several problems, namely the low level of knowledge and understanding in recording production costs, calculating and determining the total cost of production, and accuracy in determining and calculating selling prices. The purpose of this community service activity is to provide knowledge and understanding through counseling and socialization related to the problems faced by them, namely the MSMEs business actors in Majau Village. The method used in community service activities is the lecture method which is then followed by discussion, question and answer and case simulations. The evaluation that was carried out before the end of the activity showed that most of the participants really understood the counseling or socialization material delivered. The evaluation results also illustrated that all participants who attended the activity felt that they had benefited and were satisfied with the implementation of this activity. Keywords: MSMEs, Cost Of Production, Selling Price